The phytoremediation potential of non-edible oil-producing plants for gold mine tailings - Nadya Nurafifah Andriya; Hamim Hamim; SULISTIJORINI SULISTIJORINI; Triadiati Triadiati (Society for Indonesian Biodiversity, 2019)
Abstract. Andriya NN, Hamim H, Sulistijorini, Triadiati. 2019. The phytoremediation potential of non-edible oil-producing plants for gold mine tailings. Biodiversitas 20: 2949-2957. Plants can be used as phytoremediation agents to reduce environmental pollutants including heavy metal contaminants produced due to industrial activities. The objective of this study was to analyze the morphological, anatomical, and physiological responses of four non-edible oil-producing plants namely Jatropha curcas, Ricinus communis, Reutealis trisperma, and Melia azedarach and their ability to absorb and accumulate lead  (Pb) when grown in different concentrations of gold mine tailings. The study was conducted using a completely randomized design involving two factors, four different species of plants and three different concentrations of tailings  (0%, 50%, and 100%). Gold mine tailings caused a decrease in the growth of all species indicated by a significant reduction in plant height, leaf number, leaf area, shoot as well as root dry weight, while it significantly increased green RGB values of leaves. Pb accumulation was detected in the root as well as leaf tissues of the plant-based on histochemical analysis. The treatment with tailings also caused an increase in lipid peroxidation levels as indicated by increased malondialdehyde content in the roots and leaves. On the other hand, chlorophyll and carotenoid content decreased due to tailings treatment, along with the relative water content. Among the four species investigated, R. trisperma was found to be the most resistant species to gold mine tailings based on its ability to maintain growth even during gold tailing stress, which is also supported by principal component analysis.